Tarefa de discriminação de fonemas com pseudopalavras (Revista de Estudos da Linguagem, 2004)
This paper presents a task for phoneme discrimination as part of a more comprehensive set of tasks for psycholinguistic assessment of language currently under development (TAL-UFMG). The task consists of 40 pairs of monosyllabic nonwords, from which 20 pairs are made of two copies of the same syllable and 20 pairs differ in relation to one single feature (voice, place or mode of articulation) of their first consonant. This list of syllable pairs was presented in random order to 8 adult aphasic patients (experimental group) and 55 normal young adults (control group). Participants were asked to indicate after each pair whether it consisted of either equal or different syllables. The experimental group made 60.6% correct answers versus 97.5% by the control group. Differences were larger among voiced/unvoiced stimuli. The consistency ofthe task (Kuder-Richardson) for the experimental group was 0.823.Thus, the task is able to distinguish between normal and abnormal populations and, within each, between stimulus differences.